Hubungan Dzikir dengan Pengaturan Pernafasan dalam Pustaka Centhini - Muzairi Muzairi (Jurnal Filsafat "WISDOM", 2006)
Centhini is one of the suluk literatures; its main doctrine isto reach the “perfect of life”, that is the unity of human being andGod. The ways to reach the “perfect of life” by syariat, tarekat,hakikat, and ma’rifat as them said by Seh Amongraga does not asomething new, because of which has been dealt with in theprimbon that came from XVI century and Hamzah Fansuri. Salatand dzikir and breath-ordering in Centhini are the means forhuman beings to get unity to God. It appears that dzikir in theconnection to breath-ordering is an indication of universal way inmysticism that be able find out in all religions. Double function ofSeh Amongraga who gave by authors essentially has a mission tomake harmony of religion and Javanese tradition, that is thetradition of Seh Siti Jenar, Sunan Panggung, Ki Bebeluk, and SehAmongraga with Islam that purely legalistic.